Maternal Factors Associated With Infant Neurodevelopment in HIV-Exposed Uninfected Infants. (9th October 2019) - Alcaide, Maria L; Rodriguez, Violeta J; Abbamonte, John M; Ramlagan, Shandir; Sifunda, Sibusiso; Weiss, Stephen M; Peltzer, Karl; Jones, Deborah L
Abstract: Background: This study evaluated maternal factors associated with infant neurodevelopmental outcomes among HIV-exposed uninfected (HEU) infants in rural South Africa. This study followed pregnant women living with HIV pre- and postpartum and evaluated sociodemographic factors, use of antiretrovirals (ARVs), and mental health factors as predictors of HEU infant developmental outcomes (cognitive, receptive, and expressive communication, fine and gross motor skills). Methods: Participants were 80 mother–infant dyads. Mothers were assessed during pregnancy, and HEU infant development was assessed at a mean (SD) of 13.36 (1.89) months of age. Results: Women were an average (SD) of 28.9 (5.2) years of age, and infants were on average 13.4 (1.9) months old. An analysis of covariance indicated that infants whose mothers had ARV detected in dry blood spots at 32 weeks of pregnancy had lower functioning scores in the cognitive domain than those with undetected ARV (n = 14; M, 15.3 vs 17.2; P = .048). Antenatal physical intimate partner violence was also associated with delayed cognitive functioning ( F (1, 74), 4.96; P = .029). Conclusions: This study found risks for delayed infant cognitive development to be associated with the use of ARV during pregnancy and intimate partner violence, although findings merit replication due to the low sample size. Given the growing number of HEU infants, the necessity to better understand the potential toxicity of ARV exposure in utero is apparent. Similarly, the need for preventing intimate partner violence and screening for, and managing, developmental delays among these infants is increasing.